Place-based disruptions of humanism, coloniality and anti-blackness in early childhood education - Nxumalo, Fikile (Critical Studies in Teaching and Learning, 2023)
This essay engages with the generative potentials and necessity of attunement to place in education. I focus in particular on what bringing Indigenous and Black feminisms and feminist new materialisms into conversation might mobilize towards unsettling the anthropocentric, colonial, and anti-Black inheritances of early childhood education. I situate my engagements with place within ongoing and intensifying anthropogenic environmental precarity that underline the imperative of more relational ways of living and learning in always already more-than-human worlds. In bringing feminist new materialisms into conversation with Indigenous and Black feminisms, I am interested in mobilizing relationalities that unsettle human centeredness while also disrupting the universalization of the category of the human.